Improved solid-phase microextraction extraction procedure to detect trace-level epichlorohydrin in municipal water systems by HS-SPME-GC/MS - Lei, Ping; Wang, Lu; Yan, Yun; Deng, Wubin; Gao, Jingsi; Zhu, Jia; Liang, Miaoqing; Wen, Jiaheng; Lv, Jianfeng; Zhou, Jianfeng (Frontiers in Chemistry, 2022)
Epichlorohydrin (ECH) is toxic to humans via multiple routes and is a potential carcinogen. The accurate measurement of ECH at trace level (< 0.1 μg/L) is still an obstacle hindering the monitoring and regulation of municipal water systems. In this study, an improved headspace solid-phase microextraction (HS-SPME) procedure is developed and optimized to extract and enrich ECH with high sensitivity, accuracy, and precision. A total 17.4-time enhancement in signal is achieved compared with the default condition. Specifically, the activated-carbon coated SPME fiber was found to be much more effective than the pristine fiber with an enhancement of 4.4 times. The effects of different mineral salts were studied and an addition of 3 g Na₂SO₄ in the SPME head achieved an additional 3.3-time increase. The optimization of extraction conditions (pH=7, 35°C, and 20 min extraction duration) brought another 1.2 times further. Combined with gas chromatography with mass spectrometry, the optimized method exhibits curve linearity in the range of 0–1.0 μg/L with an R2 of 0.998. The limit of detection, precision, and accuracy of the method are 6 ng/L, 2.6 to 5.3%, and -3.5 to -2.0%, respectively. The recovery rates from tap and surface water were investigated, and a recovery rate of 72.5–116% was obtained. Adhering to the requirements of existing water quality regulations, our method shows a high potential to be applied in drinking water quality monitoring and water treatment process assessment.